1997
DOI: 10.1677/jme.0.0190311
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine hydroxylase and norepinephrine transporter mRNA levels increase in locus coeruleus after coitus in rabbits

Abstract: Hypothalamic norepinephrine (NE) plays an important role in the control of sexual behavior and in the secretion of gonadotropin. Our previous study showed that coitus induced simultaneous increases in hypothalamic NE and GnRH releases in female but not in male rabbits. To investigate the activities in noradrenergic neurons during the coitus-induced process of an LH surge, we measured tyrosine hydroxylase (TH, the rate-limiting enzyme in NE synthesis) and NE transporter (NET, a key protein for NE cellular reupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Note that due to high levels of GnRH in mated females, different scales were used to plot the patterns of GnRH in mated males and females. after mating (248). Likewise in male ferrets (229), mating with intromission did not significantly increase the percentage of TH-IR neurons colabeled with Fos-IR in any brain stem region.…”
Section: Norepinephrinementioning
confidence: 70%
See 1 more Smart Citation
“…Note that due to high levels of GnRH in mated females, different scales were used to plot the patterns of GnRH in mated males and females. after mating (248). Likewise in male ferrets (229), mating with intromission did not significantly increase the percentage of TH-IR neurons colabeled with Fos-IR in any brain stem region.…”
Section: Norepinephrinementioning
confidence: 70%
“…The distribution of NE cells in the rabbit is similar to that of the rat (e.g., 100). Yang et al (248) showed that the receipt of mating stimulation increased TH and NET mRNA levels in the LC of female rabbits. Likewise, in estrous ferrets (229), the receipt of an intromission significantly augmented the percentage of TH-IR neurons colabeled with nuclear Fos protein in both the LC (A6) and the rostral A2 cell groups.…”
Section: Norepinephrinementioning
confidence: 99%
“…Whether this observation in an OVX + E model can be applied to ovarian‐intact primates remains to be resolved. The selection of the locus coeruleus in this study is based on our previous findings in the rabbit that TH mRNA expression is increased in this brainstem noradrenaline area after coitus ( 41). This report does not exclude other brainstem noradrenergic areas, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The classical neurotransmitter systems via which socio-sexual stimulation modulates GnRH neurons are only poorly understood. The best documented is the noradrenergic system which is involved in male-stimulated ovulation in rabbits and ferrets (Wersinger and Baum, 1997 ; Yang et al, 1996 , 1997 ). In rabbits for example there is a parallel increase in noradrenalin (NA) and GnRH in the MBH within 10 min of mating (Kaynard et al, 1990 ).…”
Section: Classical Neurotransmitters Involvedmentioning
confidence: 99%